Sanksi Pidana terhadap Pelaku Tindak Pidana Pembuangan Limbah Bahan Berbahaya dan Beracun (B3) tanpa Ijin di Kabupaten Purwakarta - Maulana Fahmi Idris; Rengga Kusuma Putra (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
B3 waste is the residue of a business activity that contains hazardous or toxic materials due to chemical concentrations, properties and amounts that are harmful to human health and can damage the environment if not managed properly. In Karawang Regency, it is alleged that there is a criminal act of disposing of hazardous and toxic waste (B3) without a permit so that it endangers human health and damages the environment. B3) Without a Permit in Purwakarta Regency The method used in this research is normative juridical with the nature of descriptive research and technical analysis of legal materials used is a qualitative analysis technique, meaning that the analysis does not depend on numbers based on numbers, but collects data from the previously mentioned legal materials, qualifying them, connecting them with the problems discussed, then draw conclusions from the research results. The results of the first study indicate that B3 waste (hazardous and toxic materials) is the residue of a business activity that contains hazardous or toxic materials due to chemical concentrations, properties and amounts that are harmful to human health and can damage the environment if not managed properly. Criminal Sanctions Against Perpetrators of Criminal Acts of Disposal of Hazardous and Toxic Materials (B3) Permit In Purwakarta Regency, in this case the PT Assa Peper case through court decision No. 55/PID.B/LH/2016/PN.PWK, the defendant AS as Director was sentenced to 10 (ten) months in prison and a fine of Rp. 100,000,000. provided that if the fine is not paid, it must be replaced with imprisonment for 2 (two) months.